ChemInform Abstract: Application of 1, 4‐Bis(3‐methylimidazolium‐1‐yl)butane Ditribromide [bMImB]·(Br3)2 Ionic Liquid Reagent for Selective Oxidation of Sulfides to Sulfoxides. Issue 3 (29th December 2015) - Manesh, Abbas Amini; Eshbala, Fereshteh Hosseini; Hemmati, Saba; Veisi, Hojat
Abstract: No over‐oxidation is observed, allylic and alcoholic functions remain intact.